The Strategy of Nazir Development in Indonesia: A Qualitative Study - Rahmi Edriyanti; Muslim Marpaung; Sugianto; Uning Musthofiyah; Lisa Listiana (AL-MUZARA'AH, 2021)
The purpose of this study is to identify the most important factors in determining current strategies for the development of Nazir in specific region of Indonesia and to examine how the internal and external states developing in that province. Two analyses were used in this research method: SWOT (Strength, Weakness, Opportunity, and Threats) and QSPM (Quantitative Strategic Planning Matrix). The number of respondents who filled out the questionnaire was 8 big institutional Nazir and 5 Waqf experts between September and January of 2021, respectively. The result of SWOT analysis is that Waqf institutions need to carry out WT (Weakness Threats) strategy, which is a defensive strategy. Meanwhile, the QSPM analysis discovered that the second strategy is the most priority one. Afterwards, at the conclusion of this study, the results of these particular studies as well as recommendation will be discussed.